Dilacera, a new astonishing Amazonian genus of termitophilous rove beetle (Staphylinidae: Aleocharinae: Termitonannini) and updated checklist of the subtribe Termitonannina with their termite hosts - Zilberman, Bruno; Pires-Silva, Carlos M. (Zootaxa, 2022)
The subtribe Termitonannina consists of eight genera of termitophilous rove beetles from the Neotropical region associated with termites of the subfamilies Apicotermitinae, Nasutitermitinae, Syntermitinae, and Termitinae. A new genus, Dilacera Zilberman & Pires-Silva gen. nov. is established, and a new species, Dilacera exokosmos Zilberman & Pires-Silva gen. et sp. nov., from the Brazilian Amazon, is described and illustrated, with its morphological distinctiveness within the subtribe, discussed. Remarks on the host relationship with Uncitermes teevani (Emerson, 1925) (Termitidae: Syntermitinae) are provided, with an updated checklist of termitophilous species and their associated hosts within Termitonannina, including a discussion on confusing nomenclatural takes on termite hosts.